Book review: Local government in Poland and Germany, eds. Max- Emanuel Geis, Grażyna Grabarczyk, Jarosław Kostrubiec, Jerzy Paśnik, Thorsten Ingo Schmidt, Wydawnictwo Wyższej Szkoły Menedżerskiej im. Prof. Leszka J. Krzyżanowskiego, Warsaw 2015, pp. 225 - Dąbrowski, Karol (Studia Iuridica Toruniensia, 2017)
*